Influences on the Onset and Early Trajectory of Childhood Chronic Pain from a Developmental Perspective: An Integrative Review - Meys, Amanda Nicole (Auckland University of Technology, 2021)
Chronic pain typically describes pain of longer than three months duration or that has exceeded expected tissue healing timeframes. For children, chronic pain consequences involve long-term social, emotional, physical and financial impacts, with lifelong heightened pain sensitivities and dysfunction. With the prevalence of chronic pain in childhood rapidly increasing, childhood chronic pain intervention plays a role in supporting wider population health. Primary healthcare is most often, the place of initial intervention for a child in pain, and initial treatment is predictive of chronic pain risk and outcomes. Further, children’s pain experiences and responses are thought to be more modifiable than those of adults. Therefore, quality, primary healthcare interventions have the potential to positively influence the onset and early trajectory of chronic pain in children. Childhood is a period of extensive development and learning, requiring practitioners’ acknowledgement and understanding of relevant cognitive, physical, psychological and social progressions in the children they work with. Yet, clinically, application of child development theory appears limited when working with children with chronic pain, creating an adult-centric approach to practice. With diverse biological risk factors, affective concerns and complex family factors thought to impact on childhood chronic pain trajectories, practitioners experience difficulty drawing together evidence to inform management. This practice project employed an integrative review methodology. It aimed to draw together and analyse the research literature about the biopsychosocial factors influencing chronic pain onset and its early trajectory in primary school aged children using a childhood developmental lens. The research evidence was critically considered in light of sociocultural and social cognitive developmental theories. Neuropsychological and neurophysiological developmental understandings were also employed to collectively highlight relevant biological, psychological and social developmental concerns. This review contributes novel understandings about childhood chronic pain that have implications for primary health care practice. The results suggest a range of interacting biological, psychological, and social factors play a role in the early trajectory and onset of chronic pain in children, and that many of these incorporate developmental considerations. Psychological factors in particular show interactions amongst outcomes for both parents and children. Such findings suggest that at a primary healthcare level, an interdisciplinary approach is essential. A key aspect that was predominantly absent from the current research, was the measure of change over time, needed to show the variations in presentation that might occur across a child’s development. Adopting a broader, more holistic conceptual understanding of childhood development would contribute to practitioner understandings of the biopsychosocial model as applied in childhood chronic pain, promote positive healthcare interventions and avoid pathologizing what is potentially developmentally normal. True, child-centred primary healthcare interventions have the potential to positively influence or interrupt childhood chronic pain trajectories.
Keywords: Chronic Pain; Paediatrics; Child; Influence; Development; Early trajectory; Onset; Primary care